Desenvolvimento de uma ferramenta semi-automática para diagnóstico de plasmas frios aplicados à indústria de semicondutores - Cicareli, Rodrigo dos Santos (2023)
Technological applications involving plasma processing steps are quite common. With no doubt, the semiconductor industry has a relevant impact on the daily life of contemporary society. The manufacture of integrated circuits is strongly related to the technological domain of plasma assisted processes. Such processes promote deposition and/or etching of thin films, whether metallic or dielectric. Among the various plasma diagnostic techniques, the electrostatic probe (or Langmuir probe) is a versatile and low-cost tool. Through this technique, it is possible to determine electrical parameters of plasma, such as electron and ion density, mean energy of the electron distribution, floating potential and plasma potential [1]. This work intends to develop a semi-automatic numerical tool for data acquisition, conditioning and processing, aiming to determine the electrical parameters of cold plasmas, used in dry etching processes. This automation consists of data acquisition from an analog/digital converter (A/D) with the help of LabView software and the analysis of the characteristic curve of plasmas using the electrostatic probe technique for single probes through Matlab software.